The Impact of Talking Classroom in Teaching and Learning 3Rs in Public Pre-Primary Schools in Ilemela Municipality, Mwanza-Tanzania - Mugyabuso, Witness Berthesa; Tangi, Felista (International Journal of Humanities and Education Development (IJHED), 2022)
The study confined to public pre-primary schools based on assumption that early age is the best opportunity to teach children the skills of reading, writing and arithmetic (3Rs). The study aim is to assess the impact of talking classroom in teaching and learning basic 3Rs skills in public pre-primary schools in Ilemela Municipality, Mwanza, Tanzania. The study conducted in ten public primary schools which involved twenty participants whereby ten was pre-primary teachers and ten was public primary school head teachers. The study employed qualitative approach method with a case study design. In sampling technique, the study adopted convenience and purposeful sampling technique, which included critical case to obtain participants. Data collected through structured interviews, observation checklist and documentary review guideline. The study revealed that pre-primary teachers in public primary schools had positive perceptions on the use of talking classroom in teaching and learning 3Rs in pre-primary children. Also, the study revealed that for effective use of 3Rs in public pre-primary classroom, there must be enough teaching and learning materials. The study recommends that the government should ensure the increase of school capitation funds especially in primary schools.